1997
DOI: 10.1111/j.1346-8138.1997.tb02796.x
|View full text |Cite
|
Sign up to set email alerts
|

Merkel Cell Carcinoma and Multiple Bowen's Disease: Incidental Association or Possible Relationship to Inorganic Arsenic Exposure?

Abstract: An 81-year-old Japanese male was referred to our clinic in 1991 with multiple Bowen's disease. The associated hyperpigmentation of the trunk and extremities and palmoplantar keratotic nodules indicated that he had suffered from chronic arsenic poisoning. Interestingly, he was a native of Namikata in Ehime, Japan, where many residents have suffered from multiple Bowen's disease with internal malignancy. Arsenic exposure was strongly suspected. Two years later, Merkel cell carcinoma developed on the dorsum of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…The most commonly reported signs of chronic arsenic exposure in human populations include hyperpigmentation, keratosis, and skin cancer (Jaafar et al,1993; Ohnishi et al,1997). It has been proposed that hyperpigmentation and keratosis may act as an early warning signal of development of cancer in internal organs (Tello,1988; Khan et al,2003).…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly reported signs of chronic arsenic exposure in human populations include hyperpigmentation, keratosis, and skin cancer (Jaafar et al,1993; Ohnishi et al,1997). It has been proposed that hyperpigmentation and keratosis may act as an early warning signal of development of cancer in internal organs (Tello,1988; Khan et al,2003).…”
Section: Discussionmentioning
confidence: 99%
“…Additional risk factors for MCC include an age of greater than 60 years, and most MCCs occur in sun-exposed areas of the skin 110 . In addition, it has been reported that pharmacological use of statins and environmental exposure to arsenic increase the risk of developing MCC, although the mechanisms involved are unclear 111,112 .…”
Section: Merkel Cell Carcinomamentioning
confidence: 99%
“…It is also reported that Merkel cell carcinoma 43 sometimes co-exist with Bowen's disease 44,45 in patients with arsenicosis. There is also a study which has demonstrated an increased risk of melanoma in persons with elevated toenail arsenic concentrations 46 , raising the issue relating to the role of arsenic in the development of melanoma.…”
Section: Keratosismentioning
confidence: 97%